Late Roman cooking wares in the area of Barcino and Iluro: From African Imports to local production - Riutort Riera, Jeronima (Rei Cretariae Romanae Fautorum Acta, 2022)
Late Roman cooking and coarse wares in the North-West Mediterranean are the continuity and evolution of Roman imperial pottery. This study focuses on the area of Barcino and Iluro and the neighbouring regions of the latter. There can be seen evidence of the predominance of African imports that lasted from the 4th to the 6th century. From the turn of the 6th century, there was a noticeable change in that tendency owing to the progressive decrease in imports and an increase in local productions since the second half of the 7th century when imported wares were only residual. These local wares were significantly different than Roman pottery in terms of their coarser pastes, techniques, and shapes, developing a style of their own. The archaeometrical analysis of Late Roman cooking wares from rural sites of the area, confirms this autochthonous production.